Effects of co-solvent, temperature and pressure on asiaticoside content in supercritical fluid extraction of Centella Asiatica - Ruslan, Fatin Shazwani; Darnis, Deny Susanti; Bakhtiar, M. Taher; Mohammad, Nurul Farahain (2020)
Centella asiatica had been reported to possess many biological properties due to the presence of asiaticoside. In this study, the extraction of asiaticoside was done using supercritical fluid extraction as it was believed to produce highly concentrated extracts. This research focused on the effect of co-solvent percentage, pressure and temperature on the asiaticoside content. The effects of different parameters on asiaticoside were screened using Two-Level Factorial and optimized using Central Composite Design. Besides, analysis of variance at p-value < 0.05 was used to scrutinize the significance of the factors. Asiaticoside was extracted following the treatment combinations of three parameters which were co-solvent (5 – 15 %), temperature (70 – 90 °C) and pressure (1 – 20 MPa). The optimized extraction parameters were found at 10 %, 10.5 MPa and 80 °C for co-solvent percentage, pressure and temperature. The overall model was significant (p < 0.05) with acceptable R2 0.9975.